War-Time Portraits of the Gringo: American Invaders and the Manufacture of Mexican Nationalism - Colcleugh, Malcolm (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1995)
AbstractThe 1846 American invasion of Mexico sparked an intensely nationalist response among members of Mexico's Liberal and Conservative intelligentsia. This paper documents and analyzes that nationalist reaction. To rally the nation to the cause, Mexican intellectuals constructed and presented to the Mexican masses frightful, negative caricatures and stereotypes of the invading Americans. An abject race of vile and perfidious usurpers, Anglo-Saxon invaders were, the intelligentsia warned, intent upon the spoliation of Mexico and the enslavement of her people. If not stopped by a vigorous prosecution of the war, they warned, the greedy and cruel heretics from the north would soon descend over the whole nation, raping Mexico's daughters along the way and desecrating her holy shrines. Disseminated through newspapers, political pamphlets and broadsides, it was against such caricatures that the allegedly positive features of the Mexican identity were defined and delineated. Against the dark and fiendish stereotypes of the Americans stood, in stark and powerful contrast, the moral and benevolent Mexicans. Where the American caricature evoked the dreadful image of a marauding, degenerate infidel, the Mexican portraiture called forth the equally evocative image of an upright, generous defender. While the Americans fought because of their greed, the Mexicans, it was maintained, resisted for the honour of their families, their Church and their motherland.